Empowering PKK Group Mothers in Labuh Baru Barat Village as an Effort to Improve Economic Welfare of Households - Yuzalmi, Nanik; Joesyiana, Kiki; Basriani, Agustin; Susanti, Desi; Wahyuni, Sri; Harahap, Arief Rifa'i (Pasundan Community Service Development, 2024)
This service aims to identify effective strategies in improving household economic welfare through empowerment programs for PKK mothers. The method used is a participatory approach by involving group empowerment activities through training, mentoring, and skill development.This activity shows that through participatory approaches and group empowerment, PKK mothers are able to develop various creative economic businesses such as handicrafts, food production, and other services. Targeted skills training and continuous mentoring play an important role in improving business management and product marketing capabilities. From the phenomenon of partner problems, the community service team consisting of lecturers from the Persada Bunda College of Economics program decided to provide training on Empowering PKK Group Mothers as an Effort to Improve Economic Welfare. In addition, collaboration between educational institutions, local governments, and local communities is also the key to success in implementing this empowerment program. With the support and involvement of all parties, a conducive environment is created for sustainable economic growth at the household level.